PERSYARATAN STATUS BELUM KAWIN BAGI PELAMAR KERJA DALAM REKRUTMEN KERJA - I Wayan Agus Vijayantera (Fakultas Hukum Universitas Dwijendra, 2021)
Abstract Job recruitment is a process carried out by employers to find prospective workers who are in accordance with the positions and positions required by the company. Job recruitment is usually announced by the employer with several conditions as criteria for job candidates that the company needs. Requirements for unmarried status set in job recruitment can have an impact on the loss of job opportunities for prospective workers who are already married. Based on this, it is necessary to carry out an analysis with normative legal research methods regarding legal considerations to determine the requirements for unmarried status for job applicants in job recruitment and whether or not norm construction is required related to norm vacancies.regarding the stipulation of conditions in job recruitment, especially regarding the unmarried status of prospective workers. In the discussion, the legal consideration for stipulating the requirements for unmarried status in job recruitment is the absence of norms related to this matter so that it is permissible to determine the requirements for marital status in job recruitment which has become the habit as a legal basis for determining certain conditions in job recruitment. The impact of this is the loss of job opportunities by prospective workers who are already married, so it is necessary to provide legal protection, especially with the construction of norms in the hope that everyone can get fair and decent work opportunities.